A Review of Vertical Organic Transistors. (22nd January 2020) - Kleemann, Hans; Krechan, Kevin; Fischer, Axel; Leo, Karl
Abstract: Powerful electronic devices require performant short‐channel transistors. For organic electronics, though, promising low‐cost and flexible electronic circuits, high processing costs for short channel devices are not acceptable. In this regard, vertical organic transistors (VOTs) are an attractive alternative, and in fact, today they reach the highest transition frequency (40 MHz) and the highest footprint current density (>1 MA cm −2 ) among all organic transistors. Here, all VOT concepts are reviewed, while discussing device physics, integration approaches, and highlighting the recent developments. The upcoming challenges for the VOT technology are also presented with a guideline for further developments. Abstract : Vertical organic transistors (VOTs) are an attractive approach to achieve short‐channel operation and today they reach the highest operation speed and the highest currents among all organic transistors. Here, all VOT concepts are reviewed regarding device physics, integration approaches, and recent developments.